1979
DOI: 10.1111/j.1365-2648.1979.tb02997.x
|View full text |Cite
|
Sign up to set email alerts
|

The inability to transfer classroom learning to clinical nursing practice: a learning problem and its remedial plan

Abstract: The inability to transfer classroom knowledge to clinical nursing practice is a common learning problem encountered by many nursing students. Manifestations of this problem may involve both the academic performance and personal development of the students: inability to solve problems in nursing situations; inflexibility and rigidity in the exercise of nursing care; fragmentation of nursing care; and apathy towards clinical practice. Because of the seriousness of this learning problem, a plan must be formulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…To be able to make clinical decisions, nursing students have to synthesize knowledge derived from nursing, biological and social sciences, and apply this to varying patient situations ( Creedy et al 1992 , Gerrish 1992). However, DeTornay (1989) and Wong (1979) suggest that students’ ability to transfer classroom theory to clinical practice is not automatic. One strategy for developing critical thinking skills involves questioning by clinical teachers during clinical experience (McCue, 1981, Infante 1981, Chase 1983, Klassens 1988).…”
Section: Introductionmentioning
confidence: 99%
“…To be able to make clinical decisions, nursing students have to synthesize knowledge derived from nursing, biological and social sciences, and apply this to varying patient situations ( Creedy et al 1992 , Gerrish 1992). However, DeTornay (1989) and Wong (1979) suggest that students’ ability to transfer classroom theory to clinical practice is not automatic. One strategy for developing critical thinking skills involves questioning by clinical teachers during clinical experience (McCue, 1981, Infante 1981, Chase 1983, Klassens 1988).…”
Section: Introductionmentioning
confidence: 99%
“…If these perspectives are true, and a separation exists between what is taught and what is actually done, or between the theory taught and the theory supporting practice, then students will be conscious of it, and it will affect engagement (Swain et al ., 2003). 402 M. Edwards et al In what has been called the 'ideal transfer' (Wong, 1979), a consciously engaged student is more likely to be aware that what is taught is meant to be applied. Arguably, a lack of engagement in the classroom may explain why some students derive less from a clinical placement than others.…”
Section: Introductionmentioning
confidence: 96%
“…The recent work of Schmidt [13] has tended to support this, showing that material was better remembered by medical students when preceded by a clinical organiser in the form of a problem. Certainly many authors have identified the existence of difficulties in transferring material learned in one context into practice in the clinic [14,15,16], except when the contexts of learning and application are made as similar as possible and the cues for retrieval of the information are encoded with it at the time of learning [17].…”
Section: Introductionmentioning
confidence: 99%